Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1063/1.3463797
|View full text |Cite
|
Sign up to set email alerts
|

Ligand effect on uranium isotope fractionations caused by nuclear volume effects: An ab initio relativistic molecular orbital study

Abstract: We have calculated the nuclear volume term ͑ln K nv ͒ of the isotope fractionation coefficient ͑͒ between 235 U-238 U isotope pairs by considering the effect of ligand coordination in a U͑IV͒-U͑VI͒ reaction system. The reactants were modeled as ͓UO 2 Cl 3 ͔ − and ͓UO 2 Cl 4 ͔ 2− for U͑VI͒, and UCl 4 for U͑IV͒. We adopted the Dirac-Coulomb Hartree-Fock method with the Gaussian-type finite nucleus model. The result obtained was ln K nv = 0.001 90 at 308 K, while the experimentally estimated value of ln K nv is 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 22 publications
(25 reference statements)
1
33
0
Order By: Relevance
“…It has been demonstrated that, under hypoxic conditions, intracellular Cu was isotopically heavier than under normoxic conditions. This result is in agreement with the enrichment in 65 Cu in the tumor tissue of hepatocellular carcinoma with regard to the healthy surrounding tissue (9), thus suggesting that the tumor hypoxia was at the origin of the difference in Cu isotopic signature.…”
supporting
confidence: 80%
“…It has been demonstrated that, under hypoxic conditions, intracellular Cu was isotopically heavier than under normoxic conditions. This result is in agreement with the enrichment in 65 Cu in the tumor tissue of hepatocellular carcinoma with regard to the healthy surrounding tissue (9), thus suggesting that the tumor hypoxia was at the origin of the difference in Cu isotopic signature.…”
supporting
confidence: 80%
“…The recently documented permil-level 238 U/ 235 U variability on Earth (e.g. Stirling et al, 2007;Weyer et al, 2008) is likely a consequence of the nuclear field shift process, whereby variations in nuclear volume interact with changing electron densities during redox transitions (Abe et al, 2010;Bigeleisen, 1996;Fujii et al, 2006;Schauble, 2007). 238 U/ 235 U has been measured in the two most important U outputs from the ocean, reducing sediments and carbonates (e.g.…”
Section: Uranium Isotope Geochemistrymentioning
confidence: 99%
“…The observed uranium isotope fractionation among 232 U, 233 U, 234 U, 235 U, 236 U, and 238 U showed so called 'odd-even staggering' in parallel with the optical isotope shifts in the atomic emission spectral lines of the uranium isotopes; the mass-independent anomaly was observed on the odd mass number isotopes of 233 U and 235 U. These experimentally observed phenomena have been theoretically explained by Bigeleisen as the nuclear size-and-shape effect in the chemical isotope fractionations [2], and the isotopic fractionation factors α were reproduced by the computation of the energy states of all electrons in the isotopes [3].…”
Section: Introductionmentioning
confidence: 80%
“…Iron was then eluted with pure water and recharged to a small cation-exchange column. The adsorbed iron in the cation-exchange resin was eluted with 4 M HNO 3 . The eluted samples were heated to dryness to decompose organic impurities and re-dissolved with HNO 3 .…”
Section: Methodsmentioning
confidence: 99%